2015
DOI: 10.1002/gps.4275
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations of anosognosia in mild cognitive impairment and Alzheimer's disease

Abstract: The results indicated that anosognosia is common in both AD and MCI patients and associated with cognitive dysfunction and apathy in AD. The findings of this study warrant further research to delineate the mechanisms of anosognosia as it poses a challenge to treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 31 publications
5
41
1
8
Order By: Relevance
“…A negative association between awareness and MiniMental State Examination (MMSE) suggested that awareness increased as global cognitive functions declined. This finding supported the view that low awareness was related to advanced disease stages 30 . Conversely, a longitudinal assessment of a group of PwD (Alzheimer's disease, vascular dementia and mixed dementia) presented that initial discrepancies were moderate in relation to memory.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A negative association between awareness and MiniMental State Examination (MMSE) suggested that awareness increased as global cognitive functions declined. This finding supported the view that low awareness was related to advanced disease stages 30 . Conversely, a longitudinal assessment of a group of PwD (Alzheimer's disease, vascular dementia and mixed dementia) presented that initial discrepancies were moderate in relation to memory.…”
Section: Discussionsupporting
confidence: 88%
“…Among them, 13 evaluated only this domain 20,23,27,38,39,41,44,47,[50][51][52][53]55 . Ten studies evaluated awareness of cognitive and functional deficits domains 1,18,20,[33][34][35]40,45,46,54 , nine assessed cognitive and social-emotional functioning domains 12,13,17,24,28,30,36,37,49 , and three focused on cognitive and behavioral impairment domains 14,16,42 . Three researches compared awareness of cognitive, functional and behavioral impairment domains 22,25,32 and four studied the recognition of cognitive, functional, and social-emotional 15,19,29,43 .…”
Section: Resultsmentioning
confidence: 99%
“…In this context, these results may also indicate the patients' reduced awareness of memory difficulties or denial of decreasing cognitive abilities, which constitutes the common phenomenon of anosognosia in patients with beginning cognitive impairment [39]. However, there are conflicting findings regarding the presence of impaired insight and anosognosia among MCI patients, and other causes may explain our findings [40]. Facing the fact that MCI represents a transitional period preceding the development of dementia, it seems highly important to assess and to address the unmet needs of these patients at an early stage.…”
Section: Discussionmentioning
confidence: 79%
“…In an 18-month longitudinal study, patients with anosognosia at baseline had a significant increase in apathy scores during follow-up, compared with patients without anosognosia 53. Previous studies of the relationship between apathy and anosognosia in AD and MCI suggest that apathy manifests at later stages of neurodegeneration 55,56. Therefore, the current cross-sectional study in the early stages of AD might not have been able to identify this relationship between apathy and anosognosia, and longitudinal studies are required for this purpose.…”
Section: Discussionmentioning
confidence: 99%